Experimental investigation to optimize injection molding process of microfluidic device - Lin, Manfred Yongliang (2014)
Injection molding is a popular method for manufacturing microfluidic devices as it is an established technique for large scale production volumes. Devices with different geometry, features and materials will have different optimal process parameters. This study aims to optimize the replication quality of a microchannel cross section area in a micromixer device fabricated using Polymethyl methacrylate (PMMA) by applying Design of Experiment (DOE) method. Eight factors, melt and mold temperature, injection speed and pressure, holding time and pressure, cooling time, and the application of material pre-drying, were screened for significance. Melt temperature is the most significant factor, followed by mold temperature, injection speed, and hold pressure. The optimized settings were determined to be at high melt temperature, mold temperature and hold pressure, with low injection speed.